Optimalisasi Pemetaan Spasial dan Penanda Visual dalam Mendukung Pariwisata Kuliner di Koridor Jalan - Lilis Sri Mulyawati; Ardiatno Yanuadi; M. Yogie Syahbandar; Reza Maulana Idris; Salwa Nikmattul Ramadhani (Forum Kerjasama Pendidikan Tinggi, 2026)
The Suryakencana area in Bogor City is a multicultural culinary destination that offers a diversity of food businesses within a single urban space; however, information regarding the characteristics and distribution of these businesses is still not systematically managed, limiting visitors’ access to information. This community service activity aims to optimize spatial mapping and visual signage in supporting the development of culinary tourism along the Suryakencana Corridor. The partners involved are 50 culinary business owners who are members of the Suryakencana Traders Association. The implementation method uses a mixed approach, including Geographic Information System (GIS)-based spatial mapping, hotspot analysis to identify clusters of business activity, participatory stakeholder engagement, and the application of color-coded visual signage to facilitate the identification of business characteristics. Data were collected through field observations, documentation, and Pre-test and Post-test questionnaires using a Likert scale. The results show that culinary businesses are concentrated in high-activity points that serve as strategic locations for intervention. After implementation, the average perception score increased from 3.03 to 4.31, indicating improved understanding, better business practices, and increased awareness of the importance of information transparency for visitors. The intervention also encouraged a shift toward more proactive communication through the availability of visual information in the field. This activity demonstrates that the integration of spatial mapping and simple visual signage can enhance information delivery effectiveness and make it easier for visitors to determine culinary choices according to their preferences.